Remapping mission discourse : a festschrift in honor of the Rev. George Kuruvilla Chavanikamannil - George, Kuruvilla; Samuel, Simon; Joseph, P. V. (Palolil Varghese), 1963-; New Theological College (Dehra Dūn, India); I.S.P.C.K. (Organization) (2008)
Chiefly with reference to India.
Includes bibliographical references and index.
Keywords: Missions -- India; Missions -- Biblical teaching; Missions -- Theory; Evangelistic work -- Philosophy